Mechanical And Physical Properties of Wood-Plastic Composites Made of Polypropylene, Wood Flour and Nanoclay - Yadav, Sumit Manohar; Kamal, Yusoh (IJAFP, 2015)
The focus of this study was to characterize mechanical and physical properties of experimental composition prepared from nanoclays (Cloisite® 20A), wood flour (WF) and polypropylene (PP). Nanoclays with different concentrations were used as reinforcing filler for wood plastic compositions (WPCs). Maleic anhydride grafted polypropylene (MAPP) was added as a coupling agent to increase the interaction between the components of wood-plastic composites. Nanoclay based wood-plastic composites were made by extrusion process and then injection molding. Mechanical and physical properties of the as-prepared composites were evaluated. The results of strength measurements showed that the flexural modulus of the composite was increased by 56.33 % with increasing of nanoclays contents to 5 wt. %, reaching approximately 3.58 GPa compared to WPC containing 0% of nanoclays. Moreover, the flexural and tensile strengths reached their maximum values when the concentrations of nanoclays was 2.5 wt. %. When maintaining the nanoclays at a low concentration, it was well dispersed in the WPC. However, when more nanoclays (4 –5 wt. %) was introduced, the enhancing effect began to diminish because of the agglomeration of nanoclays which caused poor interfacial adhesion. The addition of nanoclays decreased the average water uptake by 13 %, compared to the control sample (without nanoclays). The improvement of physical and mechanical properties confirmed that nanoclays has good reinforcement and the optimum effect of nanoclays was archived at 2.5 wt. %.